Transition to Safe Sleep at Home Needs a Consistent Approach for NICU Babies and Their Parents. Issue 1 (January 2022) - Beal, Judy A.
Abstract : The American Academy of Pediatrics has long recommended transition to safe sleep positioning for NICU babies as soon as medically feasible before hospital discharge and sharing information about safe sleep with parents to promote safe sleep practices at home. Our pediatric nursing expert, Dr. Beal, covers the most recent report from the American Academy of Pediatrics on safe sleep practices in the NICU.